Ekphrasis in Shawna Lemay: “To make something mythical of my life” - Santos, Ariane Souza (Em Tese, 2012)
The object of analysis of this paper concerns the majority of the poems from  All the God-Sized Fruit, written by the Canadian poet Shawna Lemay. The poems were built following five ekphrastic frameworks: appropriation of artistic style, process of creation, critical analysis, narrative, and dialogue. The intertwinement of these frameworks with discussions about the processes of writing and painting helps the poet to build up her identity as woman, poet and woman-poet.